Adverse selection and financing of innovation: is there a need for R&D subsidies? - Tuomas Takalo; Tanja Tanayama (Bank of Finland, 2008)
We study the interaction between private and public funding of innovative projects in the presence of adverse-selection based financing constraints. Government programmes allocating direct subsidies are based on ex-ante screening of the subsidy applications. This selection scheme may yield valuable information to market-based financiers. We find that under certain conditions, public R&D subsidies can reduce the financing constraints of technology-based entrepreneurial firms. Firstly, the subsidy itself reduces the capital costs related to innovation projects by reducing the amount of market-based capital required. Secondly, the observation that an entrepreneur has received a subsidy for an innovation project provides an informative signal to market-based financiers. We also find that public screening works more efficiently if it is accompanied by subsidy allocation.
URN:NBN:fi:bof-20140807112
Keywords: D82; G28; H20; O30; O38; 330; adverse selection; innovation finance; financial constraints; R&D subsidies; certification